Correlation of disability with quality of life in patients with multiple sclerosis treated with natalizumab: primary results and post hoc analysis of the TYSabri ImPROvement study (PROTYS). Issue 1 (27th January 2023) - Achtnichts, Lutz; Zecca, Chiara; Findling, Oliver; Kamm, Christian P; Mueller, Stefanie; Kuhle, Jens; Lutterotti, Andreas; Gobbi, Claudio; Viviani, Camille; Villiger-Borter, Emanuela; Nedeltchev, Krassen
Abstract : Background: In patients with multiple sclerosis (MS), relapses and disability progression have been associated with decreased health-related quality of life (HRQoL). Methods: PROTYS, a prospective, multicentre, single-arm, observational study in seven Swiss MS centres, evaluated correlations between change in disability status (measured through the Expanded Disability Status Scale (EDSS)) and HRQoL changes (measured through the global Multiple Sclerosis International Quality of Life (MusiQoL) index questionnaire) in 35 patients with relapsing remitting MS on natalizumab for 1 year. In addition, several other scales were also used, such as: Multiple Sclerosis Intimacy and Sexuality Questionnaire-19, EuroQoL-5 Dimension, and Fatigue Scale of Motor and Cognitive Function. A post hoc analysis further assessed the association between HRQoL changes after 1 year and the MusiQoL subscores and other patient-reported outcome (PRO) measures. Results: At 1 year, patients were categorised into 'EDSS improved' (6/35), 'EDSS stable' (28/35) and 'EDSS worsened' (1/35). Mean disability scores decreased for 'EDSS improved' and 'EDSS stable' but increased for 'EDSS worsened'. Mean MusiQoL index score for 'EDSS improved' increased from 61.2 at baseline to 66.3 at 1 year, while the 'EDSS stable' group increased from 67.9 to 70.8. No meaningful statistical relationship was observed between EDSS group and changes in MusiQoL score. For the post hoc analysis, patients were categorised in 'MusiQoL improved' (n=21) and 'MusiQoL worsened' (n=14) groups. MusiQoL subscores for 'symptoms, ' 'psychological well-being' and 'activities of daily living', as well as scores for several related PRO measures, correlated with improvement of the MusiQoL global index. There was no correlation between the changes in MusiQoL global index and EDSS score. Conclusions: Natalizumab treatment for 1 year resulted in either improved or stable EDSS status in most patients, and although no significant relationship was observed between global HRQoL change and EDSS change, several domains of HRQoL seemed to improve with natalizumab treatment. Trial registration number: NCT02386566 .